Changes in academic work and their chair regime: the case of German Business Administration Academics - Muller-Camen, Michael; Salzeber, Stefan (2005)
Today universities around the world are becoming subject to audits and evaluations that not only open them to outside scrutiny, but also force them to compete with each other for students, staff and funding. This development is supposed to lead to radical changes to academic work in business schools. Whereas there is an intensive debate about this issue in the UK, much less is known about changes in higher education in other European countries. This paper will show through the example of German business administration academics that similar pressures might not lead to similar outcomes. In the German system, hierarchy will remain more important than the market for academic work. Although role conflicts seem to increase for academics at all hierarchical levels, the traditional regime is likely to resist any far-reaching changes. - Reproduced.
Keywords: Universities - Germany; Universities; Management education